Comparison of the Single Breath Vital Capacity Technique with the Tidal Volume Technique - Singh, Jeevan; Tandukar, Alex; Kharbuja, Kalpana (Journal of Nepal Paediatric Society, 2019)
Introduction: The single breath vital capacity (VC) induction and the tidal volume (TV) breathing induction are currently administered for inhalation of anaesthesia with sevoflurane in children. The aim of this study was to determine whether the vital capacity technique achieves more rapid induction of anaesthesia in children compared to the conventional tidal volume technique. Material and Methods: Sixty ASA physical status 1 or 2 children aged between 5 and 15 years, scheduled to undergo elective urological, orthopaedic or visceral surgery under general anaesthesia using inhalational induction with sevoflurane were recruited and randomized to receive either vital capacity induction or tidal volume induction with 8% sevoflurane at 6L/min of O2 followed by laryngeal mask airway insertion or endotracheal intubation with endotracheal tube. Time required for induction, hemodynamic changes, airway tolerance, side-effects, level of satisfaction using a visual analogue scale (0-100) and Smiley scale (0-10) were documented. Results: Induction time was significantly shorter with the vital capacity induction technique than with the tidal volume breathing induction technique (43.8 ± 13.4 seconds vs 70.8 ± 16.4 seconds; P<0.01). The time to central myosis, haemodynamic changes and respiratory events incidences were similar in both the group. Fewer complications occurred with vital capacity group. More than 94% of the children choose the single Breath Vital Capacity method of induction to the tidal volume technique. Conclusion: For inhalation induction of anaesthesia, the vital capacity induction was faster and produced less complication than that of tidal volume breathing technique.